Generating critical thinking on gender issues using listening activities (2019)
This paper contains the description of the problem we found regarding students’difficulties in taking a critical point of view towards gender issues, which is a common situation in this classroom and in nowadays’ society. By working on the listening micro skill of distinguishing between literal and implied meaning, we addressed the problem mentioned above. We applied 30 surveys to the same number of participants, and, along on, we will apply interviews, and group discussions related to the topics. Participant observation of these group discussions and the classes helped us gain insights into the progress that participants may make. We made our pedagogical intervention with lectures, recordings, videos and lectures about the topics related to sexism (Male chauvinism, feminism among others). In this paper, we also present the results and advances we evidence along the pedagogical intervention as well as the analysis of these aspects and the conclusions we get to.